Seekers and things: spiritual movements and aesthetic difference in Kinshasa - Lambertz, Peter (Berghahn, 2018)
Focusing on the intricate presence of a Japanese new religion (Sekai Kyûseikyô) in the densely populated and primarily Christian environment of Kinshasa (DR Congo), this ethnographic study offers a practitioner-orientated perspective to create a localised picture of religious globalization. Guided by an aesthetic approach to religion, the study moves beyond a focus limited to text and offers insights into the role of religious objects, spiritual technologies and aesthetic repertoires in the production and politics of difference. The boundaries between non-Christian religious minorities and the largely Christian public sphere involve fears and suspicion of 'magic' and 'occult sciences'.--Publisher's summary